Safety of a gastropexy device in infants and young children in percutaneous endoscopic gastrostomy tube placement - G. Gavallér; M. Bukva; P. Gál; P. Pásztor; A. T. Takács; Cs. Bereczki; D. Szűcs (Scientific Reports)
Abstract In our practice, there is a growing need to perform gastrostomy tube placement in infants and young children with feeding difficulties. To avoid possible complications arising from pull-through method (pull-through PEG) we began to perform a one-step endoscopic gastrostomy with a gastropexy device (push GT). This study aimed to evaluate the safety of this technique in infants and young children. In our study, 60 pull-through PEG and push GT procedures were retrospectively analysed in patients between 2.83 and 8.6 kg. We analysed the adverse events in both groups. Age, sex, weight, diagnosis, early (occurring ≤ 7 days after the procedure) and late (occurring > 7 days after the procedure) complications were compared in the two groups. Median follow-up duration was 12 months. Early minor complications occurred only in the push GT group, but this was not statistically significant. There was no significant difference between the groups regarding early major complications. Late minor complications were significantly more common in the push GT group. There were no late major complications in the push GT group, which is statistically significant. In infants and young children, push GT with a gastropexy device is a safe method to perform gastrostomy even in patients unsuitable for pull-through PEG placement.